Information bulletin of the Department of Structures of the Technology Center of the UFPI: a legitimation strategy - Magnaldo de Sá CARDOSO; Maria do Amparo Borges FERRO (Ediciones Universidad de Salamanca, 2019)
At the Federal University of Piauí (Brazil) within its Department of Structures, created in 1975, the Boletim informativo do Departamento, from the Technology Center is published, since 1985 as an instrument of scientific and professional legitimization. In the article the structure and contents of its beginnings are studied.